Effect of Profitability, and Leverage on Tax Avoidance In Manufacturing Companies Listed On The Stock Exchange In 2018 - 2020 - Nurrobani, Mohamad Rizqi; Gangodawilage, Damith (Yayasan Sinergi Kawula Muda, 2023)
Tax is one of the largest revenues in the APBN, but when compared to the realization with the target of tax revenue, it is still not appropriate. In this thesis, the authors indicate that this occurs because there is resistance by taxpayers in the form of tax avoidance. This study aims to determine the influence of Profitability and Leverage on Tax Avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2018 – 2020. The data used in this thesis is secondary data, namely financial reports obtained from the official website of the Indonesia Stock Exchange (IDX). www.idx.com). Sampling by purposive sampling obtained a sample of 10 companies with research time during 2018 - 2020. The method of analysis used was the regression test method and used SPSS version 24 for data processing. The results of this study indicate that profitability partially has a significant positive effect on tax avoidance, leverage partially has a significant positive effect on tax avoidance. Profitability and leverage simultaneously have an influence on tax avoidance.